Statins effects on diabetic retinopathy among patients with Type 2 Diabetes Mellitus - Hammad, Mohamed Anwar; Mohamed Noor, Dzul Azri; Syed Sulaiman, Syed Azhar; Elsayed, Tarek Mohamed Ali (Science Publishing Group, 2017)
Diabetic Retinopathy (DR) is the leading cause of vision loss in adults aged 20–74 years. DR classified as the fifth most common cause of preventable blindness and fifth furthermost common cause of moderate to severe visual impairment. A retrospective cohort study was performed to evaluate the prevalence of DR, and the effect of statins on the DR, among outpatients with Type 2 diabetes mellitus. The study was done at the endocrine clinic in Hospital Pulau Pinang, Malaysia. Two cohorts of 717 diabetic outpatients (559 statins user and 158 statins non-users) were investigated for demographic data and diagnosis of DR. Findings were presented as descriptive statistics. The age of 717 subjects was (55.2±14.9) years and females 367 (51.2%). About 166 (23.2%) patients had DR with age (58.2±14.9) years. From 559 (78%) outpatients were statins-user, 143 (25.6%) had DR with age (58.5±14.9) years. While the control group 158 (22%) participants, only 23 (14.6%) had DR with age (56.3±14.9) years. The relative risk (RR) for DR in the statin-user group for DR is 1.75 and excessive relative risk (ERR) 75%. The absolute risk (AR) is 11% and number need to harm (NNH) is 9. Nearly one-quarter of the subjects had diabetic retinopathy. The risk of diabetic retinopathy incidence is higher in the statins user group than statins non-user cohort.